Determination of critical parameters of drug substance influencing dissolution: a case study - Bojňanská, Erika; Kalina, Michal; Parizek, Ladislav; Bartonickova, Eva; Opravil, Tomas; Vesely, Michal; Pekar, Miloslav; Jampilek, Josef (BioMed research international, 2014)
The purpose of this study was to specify critical parameters (physicochemical characteristics) of drug substance that can affect dissolution profile/dissolution rate of the final drug product manufactured by validated procedure from various batches of the same drug substance received from different suppliers. The target was to design a sufficiently robust drug substance specification allowing to obtain a satisfactory drug product. For this reason, five batches of the drug substance and five samples of the final peroral drug products were analysed with the use of solid state analysis methods on the bulk level. Besides polymorphism, particle size distribution, surface area, zeta potential, and water content were identified as important parameters, and the zeta potential and the particle size distribution of the drug substance seem to be critical quality attributes affecting the dissolution rate of the drug substance released from the final peroral drug formulation.
Keywords: Microscopy, Electron, Scanning; chemické jevy; Particle Size; Chemical Phenomena; Solubility; Drug Liberation; rozpustnost; velikost částic; mikroskopie elektronová rastrovací; uvolňování léčiv